The relationship between different severity of COVID-19 pneumonia and arterial stiffness based on artificial intelligence analysis - Wu, Lingheng; Jin, Lin; Li, Xinyi; Zhang, Mengjiao; Chen, Jianxiong; Tang, Xiaobo; Du, Lianfang; Wang, Xifu; Li, Zhaojun; Luo, Xianghong (Frontiers in Medicine, 2025)
Rationale and objectivesThis study aimed to investigate the correlation between the severity of pulmonary infection and arterial stiffness pulse in coronavirus disease 2019 (COVID-19) patients using artificial intelligence (AI) quantitative analysis.Materials and methodsA total of 100 COVID-19 patients (with a mean age of 76 years) were enrolled in this study and were stratified into three groups based on the severity of their condition: mild, moderate, and severe. An AI imaging diagnostic system was used for automatic identification and quantitative analysis of infected lesions. Arterial stiffness was evaluated using the arterial velocity pulse index (AVI). Multiple linear regression analyses were performed to investigate the independent associations between the AVI, inflammatory markers, and radiographic parameters. Hazard ratios and Kaplan–Meier curves were produced to assess the association between arterial stiffness and radiographic parameters in relation to the composite outcome of all-cause mortality.ResultsThe AVI was elevated in the moderate and severe groups compared to the mild COVID-19 group (p < 0.001). Multiple linear regression analyses showed that the AVI was associated with the highest percentage of lobe infection (β = 0.813, 95%CI, 0.056–0.394, p = 0.011). Multivariable Cox regression showed that an AVI ≥ 33 was associated with all-cause mortality hazard ratio, 16.201 [95% confidence interval (CI), 1.601, 163.987].ConclusionAs the severity of pneumonia infection increased in COVID-19 patients, vascular endothelial function was impaired, leading to increased arterial stiffness. The AVI was associated with the highest percentage of lobe infection, and the severity of pneumonia was identified as an independent risk factor for increased arterial stiffness. Worsening arterial stiffness poses an increased risk of death in COVID-19 patients.